Increased hydraulic constraints in Eucalyptus plantations fertilized with potassium - Guillemot, Joannès; Asensio, Verónica; Bordron, Bruno; Nouvellon, Yann; le Maire, Guerric; Bouillet, Jean-Pierre; Domec, Jean-Christophe; Delgado Rojas, Juan Sinforiano; Abreu-Junior, Cassio Hamilton; Battie-Laclau, Patricia; Cornut, Ivan; Germon, Amandine [UNESP]; et al. (Wiley, 2021)
Fertilization is commonly used to increase growth in forest plantations, but it may also affect tree water relations and responses to drought. Here, we measured changes in biomass, transpiration, sapwood-to-leaf area ratio (As:Al) and sap flow driving force (ΔΨ) during the 6-year rotation of tropical plantations of Eucalyptus grandis under controlled conditions for throughfall and potassium (K) fertilization. K fertilization increased final tree height by 8 m. Throughfall exclusion scarcely affected tree functioning because of deep soil water uptake. Tree growth increased in K-supplied plots and remained stable in K-depleted plots as tree height increased, while growth per unit leaf area increased in all plots. Stand transpiration and hydraulic conductance standardized per leaf area increased with height in K-depleted plots, but remained stable or decreased in K-supplied plots. Greater Al in K-supplied plots increased the hydraulic constraints on water use. This involved a direct mechanism through halved As:Al in K-supplied plots relative to K-depleted plots, and an indirect mechanism through deteriorated water status in K-supplied plots, which prevented the increase in ΔΨ with tree height. K fertilization in tropical plantations reduces the hydraulic compensation to growth, which could increase the risk of drought-induced dieback under climate change.
Keywords: allometry; Eucalyptus grandis; Huber value; hydraulic conductance; potassium fertilization; transpiration; tree height; tropical forest plantation; water potential; water stress